Frank Einstein and the space-time zipper - Scieszka, Jon (Scieszka, Jon. Frank Einstein, 2018)
"Frank Einstein (kid-genius, scientist, and inventor) and his best friend, Watson, along with Klink (a self-assembled artificial-intelligence entity) and Klank (a mostly self-assembled and artificial almost intelligence entity), once again find themselves in competition with T. Edison, their classmate and archrival, this time studying the science and mysteries of the universe!"--